The art of M&A integration : - Lajoux, Alexandra Reed (McGraw-Hill, 2006)
Your roadmap to success in the world of postmerger integration Nearly half of today's executives attribute M&A failure to poor integration between merging businesses. This thoroughly revised edition of The Art of M&A Integration provides you with updated facts on integration of compensation plans, new FASB and GAAP accounting rules, strategies for merging IT systems and processes, and more.